The Factory Voice - Lynes, Jeanette (Coteau Books, 2009)
Wrapped around the stories of these four women, is a mystery. Something''s gone wrong with the Mosquitos being built for the war effort -- they keep crashing in flight tests, for no apparent reason. Is the problem with their design, or are they being sabotaged? By whom? The traitorous Red Finns? The political subversives who have recently escaped from one of the nearby prison camps? Everyone''s on high alert, and "The Factory Voice" keeps abreast of the details. Or at least the rumours. --Publisher's description
Keywords: 1939-1945; Airplane factories; Airplane factories Fiction; Amitié féminine Romans, nouvelles, etc; Avions Usines Romans, nouvelles, etc; Canada; Female friendship; Female friendship Fiction; Fiction; Guerre mondiale, 1939-1945 Femmes Romans, nouvelles, etc; Historical fiction; Northern Ontario; Ontario, Northern Fiction; Women; World War, 1939-1945 Canada Fiction; World War, 1939-1945 Women Fiction